2010
DOI: 10.1016/j.bbrc.2010.06.114
|View full text |Cite
|
Sign up to set email alerts
|

Flap loop of GluD2 binds to Cbln1 and induces presynaptic differentiation

Abstract: Glutamate receptor delta2 (GluD2) is selectively expressed on the postsynaptic spines at parallel-fiber (PF)-Purkinje neuron (PN) synapses. GluD2 knockout mice show a reduced number of PF-PN synapses, suggesting that GluD2 is involved in synapse formation. Recent studies revealed that GluD2 induces presynaptic differentiation in a manner dependent on its N-terminal domain (NTD) through binding of Cbln1 secreted from cerebellar granule neurons. However, the underlying mechanism of the specific binding of the NT… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2011
2011
2021
2021

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 24 publications
0
3
0
Order By: Relevance
“…To determine the molecular basis for GluD1-mediated regulation of inhibitory synapses, we took advantage of the recent crystallographic analysis of the interactions between GluD, Cbln, and neurexin and the abundant literature on the structure/function of GluD2 (Cheng et al., 2016, Elegheert et al., 2016, Kakegawa et al., 2007, Kakegawa et al., 2009, Kuroyanagi and Hirano, 2010, Yuzaki and Aricescu, 2017). GluDs, as all members of the iGluR family, are tetrameric receptors (Traynelis et al., 2010).…”
Section: Resultsmentioning
confidence: 99%
“…To determine the molecular basis for GluD1-mediated regulation of inhibitory synapses, we took advantage of the recent crystallographic analysis of the interactions between GluD, Cbln, and neurexin and the abundant literature on the structure/function of GluD2 (Cheng et al., 2016, Elegheert et al., 2016, Kakegawa et al., 2007, Kakegawa et al., 2009, Kuroyanagi and Hirano, 2010, Yuzaki and Aricescu, 2017). GluDs, as all members of the iGluR family, are tetrameric receptors (Traynelis et al., 2010).…”
Section: Resultsmentioning
confidence: 99%
“…On the other hand, more recent studies demonstrated that postsynaptic GluD2 induces the differentiation of PF presynaptic terminals [14][15][16]. The flap loop in the extracellular N-terminal domain of GluD2 binds to cerebellin precursor protein (Cbln) secreted from PFs [17], and Cbln binds to neurexin on the presynaptic membrane of PFs [15,18]. The GluD2-Cbln-neurexin interactions contribute to the formation, maturation and/or maintenance of PF-PC synapses.…”
Section: Introductionmentioning
confidence: 99%
“…Discrepancy of phenotypes between ts3 and other grid2 mutants suggests that the ts3 mutation, which disrupts the majority of the coding region but retains N-terminal portion of the protein, causes phenotypic differences when compared with other mutants. It has been reported that the N-terminal domain of GluD2 (Arg321-Trp339) [37], which is deleted in ts3 mutants, is crucial for Cbln1 binding and induction of presynaptic differentiation, suggesting at least that GluD2 ts3 does not function through binding to Cbln1. Alternatively, there is a possibility that another gene is also mutated in ts3 mutants.…”
Section: Discussionmentioning
confidence: 99%